Chemical composition of rhizome oleoresin and anti-inflammatory, antinociceptive and antipyretic activity of oleoresins of Alpinia allughas Roscoe. from tarai region of Uttarakhand - Ravendra Kumar; Sonali Sethi; Om Prakash; Anil Kumar Pant; Mahesh Kumar; Valery A. Isidorov; Lech Szczepaniak (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2017)
ABSTRACT The investigation of volatile constituents of the rhizome oleoresin of Alpinia allughas Roscoe. growing in tarai region of Kumaun hills, Uttarakhand, revealed the presence of 55 terpenoids. The major constituents identified in the rhizome oleoresin were α-eudesmol (21.3%), β-selinene (13.9%), valencene (9.6%), borneol (7.1%), α-humulene (5.3%) and 7-epi-α-selinene (5.2%). Other minor constituents identified were (E)-β-caryophyllene (3.8%), (6 E)-nerolidol (3.5%), (E,E)-farnesol (3.2%), caryophyllene oxide (2.5%), humulene oxide (2.7%), bornyl acetate (1.9%), coranarin- E (1.8%), linalool (1.8%) and α-terpineol (1.6%). The total identified constituents contribute 97.0% of the oleoresin. The rhizomes oleoresins exhibited significant antinociceptive activity with 34.79% inhibition at 50 mg/kg body weight and 43.24% at 100 mg/kg body wt. compare to standard drug ibuprofen (40 mg/kg body wt.), it also showed antipyretic activity in dose dependent manner with temperature reduction 77.57±5.88% at 50 mg/kg body wt. and 98.95±3.95% at 100 mg/kg body wt. after 3 hours. Oleoresin also showed 29.23% inhibition in carrageenin-induced paw edema at 50 mg/kg body wt. and 39.92% inhibition at 100mg/kg body wt. in compare to ibuprofen 40.06% at 40 mg/kg body weight.Keywords Alpinia allughas Roscoe.; Zingiberaceae; α-eudesmol; β-selinene; anti-inflammatory; antinociceptive; antipyretic activity; oleoresins